2016
DOI: 10.1177/1744806916646111
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal cell lines as model dorsal root ganglion neurons

Abstract: BackgroundDorsal root ganglion neuron-derived immortal cell lines including ND7/23 and F-11 cells have been used extensively as in vitro model systems of native peripheral sensory neurons. However, while it is clear that some sensory neuron-specific receptors and ion channels are present in these cell lines, a systematic comparison of the molecular targets expressed by these cell lines with those expressed in intact peripheral neurons is lacking.ResultsIn this study, we examined the expression of RNA transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 58 publications
10
96
0
Order By: Relevance
“…On the contrary, ND7-23 cells are derived from a fusion clone of rat DRG cells with a mouse neuroblastoma cell line, generating a more homogenous population of sensory-like neurons (Wood et al, 1990). A transcriptome analysis of these neuronal populations indicates expression of common molecular markers such as RET (a marker for myelinated and unmyelinated neurons), tyrosine hydroxylase (TH), tyrosine receptor kinase A (TrkA), and transient receptor potential channel subunits (TRP) (Yin et al, 2016). However, there are noticeable differences in the expression of several ion channels and signalling molecules (Yin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, ND7-23 cells are derived from a fusion clone of rat DRG cells with a mouse neuroblastoma cell line, generating a more homogenous population of sensory-like neurons (Wood et al, 1990). A transcriptome analysis of these neuronal populations indicates expression of common molecular markers such as RET (a marker for myelinated and unmyelinated neurons), tyrosine hydroxylase (TH), tyrosine receptor kinase A (TrkA), and transient receptor potential channel subunits (TRP) (Yin et al, 2016). However, there are noticeable differences in the expression of several ion channels and signalling molecules (Yin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A transcriptome analysis of these neuronal populations indicates expression of common molecular markers such as RET (a marker for myelinated and unmyelinated neurons), tyrosine hydroxylase (TH), tyrosine receptor kinase A (TrkA), and transient receptor potential channel subunits (TRP) (Yin et al, 2016). However, there are noticeable differences in the expression of several ion channels and signalling molecules (Yin et al, 2016). Although HSV infection altered the functional expression of T-type Ca 2+ channels in differentiated ND7-23 cells but not DRG neurons, it remains to be determined whether this regulatory mechanism interferes with channel expression in other major targets of HSV-1 infection such as trigeminal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that basal intracellular Ca 2+ concentration is sufficient to cause preassociation of calmodulin with TRPA1, but the channels are far from saturated by endogenous calmodulin. We and others have previously shown that this cell line is a suitable model which maintains broad functional similarities with dorsal root ganglia neurons [30,31], including phospholipase C pathway and PIP 2 signaling [32,33]. We reasoned that if PIP 2 binds at the same site under native conditions, then chelating background Ca 2+ should release the prebound Ca 2+ /calmodulin complex from the channel and enable it to interact with PIP 2 .…”
Section: Specific Peptides Interfere With Trpa1 Calciumdependent Potementioning
confidence: 99%
“…Previous studies have shown that T-type calcium channel was closely related to the chronic neuropathic pain and spinal cord neurotoxicity induced by local anaesthetics. Meanwhile, DRG neurons, as the primary afferent neurons, play an important role in the chronic neuropathic pain and local anaesthetics spinal cord neurotoxicity [17][18][19]. The expression of Cav3.3 calcium channel in DRG neurons was abundant, which indicated that Cav3.3 may play an important role in DRG neurons.…”
Section: Efficiency Of Pad-cav33 Shrna Recombinant Adenovirus Infectmentioning
confidence: 98%